Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Dimensi Servqual Terhadap Loyalitas Pelanggan Dengan Metode Structural Equation Modelling - Jondry A Hetharie; Simson Natten; Abraham Rieuwpassa (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
The research entitled the role of service quality on customer satisfaction and its impact on consumer loyalty in PDAM dobo city is based on problems related to customer satisfaction in this case related to the quality of service that is not optimal. The purpose of this study was to determine the effect of tangibles, responsiveness, reliability, assurance and emphaty on satisfaction and its impact on the loyalty of PDAM Dobo City service users. The population of this study was all PDAM customers in Dobo city with a sample of 98 respondents. Data collection method with questionnaire method The analysis test tool used is SmartPLS v.3.2.7 with the SEM (Structural Equation Modeling) analysis method. The results of this study show that the servqual dimension has a positive and significant effect on consumer loyalty and the satisfaction variable has been proven to mediate the relationship between the influence of the servqual dimension on the loyalty of service users in PDAM Dobo city.